Letramento Ambiental e Educação Geográfica: Uma contribuição para os Anos Iniciais do Ensino Fundamental - Martins, Betânia de Oliveira (2024)
When a child learns to read, letters that were previously enigmatic gain meaning, this is the power of literacy. When it comes to the initial years of Elementary School, literacy teachers use different teaching tools, including complementary activities, to meet the demands of the National Common Curricular Base – BNCC, which regulates the Brazilian Basic Education curriculum. From this perspective, this thesis defends the possibility of including Environmental Education – EA, together with geographic knowledge in the initial years, precisely from the 1st to the 3rd year, to aid literacy and, at the same time, in the development of environmental literacy. The choice of the topic is justified by the urgency of becoming environmentally aware and, therefore, it is important to address this issue in the first years of life. By understanding the theme, we seek to answer the following question: how can EE and Geography contribute to the process of literacy and environmental literacy in the early years? In the search for answers, the general objective of the research is to understand the dynamics of literacy from the perspective of EA and Geography through the students' living spaces. From this perspective, the specific objectives are: a) to relate EE and geographic studies in literacy from the 1st to the 3rd year of Elementary School; b) analyze the factors of child development and the processes of literacy and environmental literacy in line with Geography, through living spaces; c) propose EE activities and geographic knowledge for literacy and environmental literacy and d) discuss the evaluations presented by the research participants. The scientific method of the thesis is qualitative in nature and the methodological path is limited to bibliographical research, with an emphasis on the development of complementary EE activities and geographic knowledge for literacy and environmental literacy in the initial years. Based on the above, it was decided to use questionnaires as a research tool, which were sent along with the proposed activities to the participating teachers. After returning the questionnaires evaluated by thirty-three teachers, satisfactory results were obtained in the use of Geography and EA in literacy. To conclude, the research fulfilled the proposed objectives, as well as contributing to the production of new ideas for working Geography together with EA in literacy and environmental literacy from the first school years. This thesis is expected to contribute to the formation of new readers who are more aware and reflective about the importance of taking better care of planet Earth.